Untreated Patients Dying With AIDS Have Loss of Neocortical Neurons and Glia Cells - Kaalund, Sanne Simone (Front Neurosci, 2020)
Untreated human immunodeficiency virus (HIV) depletes its host CD4 cells, ultimately leading to acquired immunodeficiency syndrome (AIDS). In brain, the HIV confines itself to astrocytes and microglia, the resident brain macrophages, but does not infect oligodendrocytes and neurons. Nonetheless, cognitive symptoms associated with HIV and AIDS are attributed to loss of axons and white matter damage. We used design-based stereology to estimate the numbers of neocortical neurons and glial cells (astrocytes, oligodendrocytes, and microglia), in a series of 12 patients dying with AIDS before the era of retroviral treatments, and in 13 age-matched control brains. Relative to the control material, there was a 19% loss of neocortical neuron (p = 0.04) and a 29% reduction of oligodendrocytes (p = 0.003) in the patients with AIDS, whereas astrocyte and microglia numbers did not differ between patients and controls. Furthermore, we saw a 17% reduction in mean hemispheric volume in the AIDS group (p = 0.0015), which was driven by neocortical and white matter loss (p < 0.05), while the archicortex, subcortical gray matter, and ventricular volumes were within normal limits. Our results confirm previous reports of neuronal loss in AIDS. The new finding of oligodendrocyte loss supports the proposal that HIV in the brain provokes demyelination and axonal dysfunction and suggests that remyelination treatment strategies may be beneficial to patients suffering from HIV-associated neurocognitive deficits.